Review of Simulation in Pediatrics: The Evolution of a Revolution - Ojha, Rahul; Liu, Anthony; Rai, Deepak; Nanan, Ralph (Frontiers in Pediatrics, 2015)
Recent changes in medical education have highlighted the importance of experiential learning. Simulation is one model that has gained significant attention in the last decade and has been widely adopted as a training and assessment tool in medical education. Paediatric simulation has been utilized to teach various skills including resuscitation and trauma management, procedural skills and team training. It is also a valuable tool for health care educators, as it allows learners to achieve competence without putting patients at risk. Recent literature demonstrates increased retention of knowledge and skills after simulation based training. Further research is required to improve current simulation curriculums, develop validated assessment tools and to demonstrate improved clinical outcomes after simulation based training. We conducted an online search of original and review articles related to simulation and paediatric medical education and provide an overview of the role and utility of simulation in paediatrics.